2010
DOI: 10.1177/0959683609351902
|View full text |Cite
|
Sign up to set email alerts
|

A 500-year record of summer near-ground solar radiation from tree-ring stable carbon isotopes

Abstract: Tree-ring stable carbon isotope ratios (d13C) in environments of low moisture stress are likely to be controlled primarily by photosynthetic rate. Therefore, sunshine, rather than temperature, represents the more direct controlling factor. Temperature reconstructions based on tree-ring d13C results thus rest on the assumption that temperature and sunshine are strongly coupled. This assumption is tested using a d13C series from pine trees in NW Norway, where there are long (>100 yr) records of both summer te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
116
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(123 citation statements)
references
References 52 publications
5
116
0
Order By: Relevance
“…We explored the potential reduction of PAR by late-lying snow cover by calculating the PAR for days without snow and with temperature > 0 • C. The correlation between snow-free PAR0 and total carbon accumulated over the last 1000 yr was not significant (p = 0.23), so cloudiness is the more likely cause of change in PAR and carbon accumulation. The idea that the Northern Hemisphere LIA was characterised by greater summer cloudiness is consistent with historical documentary data (Grove, 2004), although recent findings from δ 13 C in Fennoscandian tree ring studies suggest that there may have been regional differentiation of this tendency (Young et al, 2010;Gagen et al, 2011).…”
Section: Climate Controls On Carbon Accumulationsupporting
confidence: 62%
“…We explored the potential reduction of PAR by late-lying snow cover by calculating the PAR for days without snow and with temperature > 0 • C. The correlation between snow-free PAR0 and total carbon accumulated over the last 1000 yr was not significant (p = 0.23), so cloudiness is the more likely cause of change in PAR and carbon accumulation. The idea that the Northern Hemisphere LIA was characterised by greater summer cloudiness is consistent with historical documentary data (Grove, 2004), although recent findings from δ 13 C in Fennoscandian tree ring studies suggest that there may have been regional differentiation of this tendency (Young et al, 2010;Gagen et al, 2011).…”
Section: Climate Controls On Carbon Accumulationsupporting
confidence: 62%
“…Gagen et al (2011) have also found high correlations of their δ 13 C series with cloud cover and sunshine and with summer temperature. Young et al (2010) showed that temperature and cloud cover may be in phase (positively correlated) or in opposition (negatively correlated), which explained the divergence between the δ 13 C series and temperature over the reconstructed 500-years period of their study. In northeastern Canada, we do not exclude the possibility that δ 13 C series could, additionally to temperature, be correlated to sunshine or cloud cover over the last millennium.…”
Section: Proxy Interpretationmentioning
confidence: 99%
“…However, because moisture is rarely the dominant tree-growth limiting factor across much of the Arctic region, there 10 is a limitation of the hydroclimate information that can be reconstructed using the isotopic approach. Using a multiparameter approach several studies (Loader et al, 2013;Young et al, 2010;2012;Gagen et al, 2011) provided sunshine/cloud estimates and were able to demonstrate large-scale shifts in the dominance of Arctic and Maritime air masses over the Northern Fennoscandian region during the Little Ice Age and Mediaeval period. Such multi-parameter studies are potentially very powerful as they help to develop testable hypotheses relating to the future response of the Arctic atmosphere 15 and provide a foundation for developing a circum-polar isotope network to track changes in atmospheric circulation and its relationship to climate throughout the Common Era.…”
Section: Stable Isotopes In Tree Rings 20mentioning
confidence: 99%
“…Waterhouse et al, 2000;Holzkämper et al, 2008;2012;Sidorova et al, 2008;Porter et al, 2009). The combination of long-lived trees, robust dendrochronologies and excellent sample preservation both on land and in lakes have facilitated the development of several multi-centennial to millennial length isotopic records (Boettger et al, 2003;Kremenetski et al, 2004;Sidorova et al, 2008;Young et al, 2010;Gagen et al, 2011;Loader et al, 2013;Porter et al, 2014). However, because moisture is rarely the dominant tree-growth limiting factor across much of the Arctic region, there 10 is a limitation of the hydroclimate information that can be reconstructed using the isotopic approach.…”
Section: Stable Isotopes In Tree Rings 20mentioning
confidence: 99%